Palouse Wars ; Indian Wars, 1858 [videorecording (DVD)] - Hengen, Nona L. (Nona Hengen, 1980)
Explores the confrontations between the U.S. Army and the Coeur d'Alene, Spokane, and Yakima Indians in 1858.